Ore genesis of the Chazangcuo Cu-Pb-Zn deposit in Tibet: evidence from mineralogy, fluid inclusions, S-Pb isotopes, and elemental geochemistry - Li, Yan; Wang, Jianguo; Yu, Zezhang; Wei, Shengyun; Ren, Haidong; Ma, Ming; Wang, Zhinan; Hu, Jian (Frontiers in Earth Science, 2024)
The Chazangcuo copper-lead-zinc deposit (hereafter referred to as the Chazangcuo deposit) is situated in the northern portion of the western section of the Gangdese polymetallic metallogenic belt in Tibet, with ore bodies strictly governed by Linzizong Group magmatic rocks and EW-trending faults. This study aims to ascertain the mineralization periods, sources of ore-forming materials, metallogenic physicochemical conditions, and genesis of this deposit. Based on comprehensive field geological surveys, sampling, and microscopic examination of petrological and mineralogical characteristics, we perform qualitative and quantitative geochemical analyses of major elements, trace elements, and rare earth elements (REEs), fluid inclusions, and sulfur and lead isotopes. The findings reveal that the mineralization process of the Chazangcuo deposit can be divided into three periods and four stages: the magmatic-hydrothermal, hydrothermal, and supergene mineralization periods sequentially, which consist of the mineralization stages of quartz-pyrite-sphalerite, medium-low-temperature hydrothermal sulfides, chlorite-carbonate minerals, and supergene oxidation in a chronological order. The ore-forming fluids prove to be medium-low-temperature low-density fluids, and the ore-forming materials are characteristic of upper crustal-derived materials. The ore-forming environment is a medium-low mineralization temperature, a shallow and weakly reducing environment. Overall, the Chazangcuo deposit is identified as a medium-low-temperature magmatic-hydrothermal deposit. The metallogenic model has the vertical zoning characteristics of lead-zinc in the upper part and copper in the lower part.